Increasing the interval of convergence for a generalized Newton’s method of solving nonlinear equations - Gromov, A.N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2016)
An approach to the construction of an extended interval of convergence for a previously proposed generalization of Newton’s method to solve nonlinear equations of one variable. This approach is based on the boundedness of a continuous function defined on a segment. It is proved that, for the search for the real roots of a real-valued polynomial with complex roots, the proposed approach provides iterations with nonlocal convergence. This result is generalized to the case transcendental equations.